Infinite variety : women in society and literature - Zaman, Niaz.; Azim, Firdous, 1952- (Dhaka : University Press, 1994)
Contributed articles.
Includes bibliographical references.
Keywords: Women and literature; Women and literature -- Bangladesh; Bengali literature -- History and criticism; Women -- Bangladesh -- Social conditions